Induction of a robust immune response against avian influenza virus following transdermal inoculation with H5-DNA vaccine formulated in modified dendrimer-based delivery system in mouse model - Bahadoran, Azadeh (Dove Medical Press, 2017)
This study was aimed to evaluate the immunogenicity of recombinant plasmid deoxyribonucleic acid (DNA), pBud-H5-green fluorescent protein (GFP)-interferon-regulatory factor (IRF)3 following delivery using polyamidoamine (PAMAM) dendrimer and transactivator of transcription (TAT)-conjugated PAMAM dendrimer as well as the effect of IRF3 as the genetic adjuvant. BALB/c mice were vaccinated transdermally with pBud-H5-GFP, PAMAM/pBud-H5-GFP, TAT-PAMAM/pBud-H5-GFP, and TAT-PAMAM/pBud-H5-GFP-IRF3. The expression analysis of H5 gene from the blood by using quantitative real-time reverse transcriptase polymerase chain reaction confirmed the ability of PAMAM dendrimer as a carrier for gene delivery, as well as the ability of TAT peptide to enhance the delivery efficiency of PAMAM dendrimer. Mice immunized with modified PAMAM by TAT peptide showed higher hemagglutination inhibition titer, and larger CD3+/CD4+ T cells and CD3+/CD8+ T cells population, as well as the production of cytokines, namely, interferon (IFN)-γ, interleukin (IL)-2, IL-15, IL-12, IL-6, and tumor necrosis factor-α compared with those immunized with native PAMAM. These results suggest that the function of TAT peptide as a cell-penetrating peptide is able to enhance the gene delivery, which results in rapid distribution of H5 in the tissues of the immunized mice. Furthermore, pBud-H5-GFP co-expressing IRF3 as a genetic adjuvant demonstrated the highest hemagglutination inhibition titer besides larger CD3+/CD4+ and CD3+/CD8+ T cells population, and strong Th1-like cytokine responses among all the systems tested. In conclusion, TAT-PAMAM dendrimer-based delivery system with IRF3 as a genetic adjuvant is an attractive transdermal DNA vaccine delivery system utilized to evaluate the efficacy of the developed DNA vaccine in inducing protection during challenge with virulent H5N1 virus.